Towards Carbon Neutral Airport Operations Through the Use of Renewable Energy Sources: The Case of Chhatrapati Shivaji Maharaj and Indira Gandhi International Airports, India - Baxter, Glenn (International Journal of Environment, Agriculture and Biotechnology, 2023)
A very significant development in the global airport industry in recent times has been the introduction and use of green renewable energy systems, such as solar and wind powered hybrid systems. Airports are very energy intensive and have a significant carbon footprint. Thus, the use of renewable green energy is enabling airports to reduce their carbon footprint thereby mitigating their environmental impact. Using an in-depth instrumental case study research design, this study has examined the use of renewable green energy systems by Delhi’s Indira Gandhi Airport and Mumbai’s Chhatrapati Shivaji Maharaj International Airport. The case study revealed that Chhatrapati Shivaji Maharaj International Airport has entirely switched to green sources for its energy consumption needs, thereby making it one of India’s 100 per cent sustainable airports. In April 2022, Mumbai Airport enhanced its usage of green energy when it deployed a 10Kwp Hybrid SolarMill consisting of 2Kwp TurboMill (three Savonious vertical axis type wind turbine (VAWT) and 8Kwp Solar PV modules. The new system has enabled Chhatrapati Shivaji Maharaj International Airport to reduce its carbon footprint as the new system will reduce its carbon dioxide (CO2) emissions by 120,000 tonnes per year. In 2022, Delhi’s Indira Gandhi Airport became the first airport in India to be powered entirely by hydro and solar energy sources. This energy-related measure is one of the airport’s key actions to realize its 2030 objective of being a Net Zero Carbon Emission Airport. By moving to renewable sources for its energy requirements, the airport is expected to reduce its carbon footprint by around 200,000 tons of carbon dioxide (CO2) emissions per annum. The use of green energy sources has helped the airports to mitigate the harmful environmental impact from the use of fossil-based fuels